Goldenaster, Chrysopsis - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Two species of goldenaster are found on beach dunes within the western Panhandle of Florida (FNAI 2000). Chrysopsis gossypina subsp. Cruiseana (Cruise’s goldenaster) and Chrysopsis godfreyi (Godfrey’s goldenaster), which is further differentiated into two morphologically distinct forms, Chrysopsis godfreyi f. godfreyi and Chrysopsis godfreyi f. viridis. https://edis.ifas.ufl.edu/sg166